The SIRT1-c-Myc axis in regulation of stem cells - Fan, Wei; Li, Xiaoling (Frontiers in Cell and Developmental Biology, 2023)
SIRT1 is the most conserved mammalian NAD+-dependent protein deacetylase. Through deacetylation of transcriptional factors and co-factors, this protein modification enzyme is critically involved in metabolic and epigenetic regulation of stem cells, which is functionally important in maintaining their pluripotency and regulating their differentiation. C-Myc, a key member of Myc proton-oncogene family, is a pivotal factor for transcriptional regulation of genes that control acquisition and maintenance of stemness. Previous cancer research has revealed an intriguing positive feedback loop between SIRT1 and c-Myc that is crucial in tumorigenesis. Recent literature has uncovered important functions of this axis in regulation of maintenance and differentiation of stem cells, including pluripotent stem cells and cancer stem cells. This review highlights recent advances of the SIRT1-c-Myc axis in stem cells.